Enhancement of the design of air-conditioning heat exchangers circuits / Phan Choon Kit - Phan, Choon Kit (2018)
The important of delivering a higher capability heat exchanger had been identified in the study. The circuit of the heat exchanger is proposed to improve in term of the circuit design. Literatures studied had been performed to acquire various possibilities to improve on the heat exchanger capacity. Several researches had been studied and benchmarked due to the improvement leads by the respective design. A heat exchanger circuitry has been enhanced to deliver higher capacity by using CoilDesigner. Simulation had been performed to estimate the performance of the heat exchanger by changing the design and configuration of the circuitry. The simulated model is being validated by experiment data. Similar researches are being benchmarked to provide reliable justification. Several improvements acquired based on the study on the suggestion of literature review had contributed to improvement of the circuit in this study. Some measures and design proposed had positive impact toward the performance of the heat exchanger. The optimized number of circuitry for this design is being studied and acquired. The fin pattern has also changed from louver pattern to slit fin pattern. The air side capacity of the heat exchanger has increased by 8.46% after adopting some of the design change proposed throughout the study.